Monetary policy and unemployment : the US, Euro-area and Japan - Semmler, Willi (London : Routledge, 2005)
This book pulls together papers presented at a conference in honour of the 1981 Nobel Prize Winner for Economic Science, the late James Tobin. Among the contributors are Olivier Blanchard, Edmund Phelps, Charles Goodhart and Marco Buti. One of the main aims of the conference was to discuss what potential role monetary policy has on economic activity and unemployment reduction in three key currency zones - the United States, European Union and Japan.
"Papers presented at a conference hosted by the Economics Dept. and the Centre for Economic Policy Analysis of the New School University held from Nov. 22-23, 2002."_T.p verso.
Formerly CIP.
Includes bibliographical references and index
rpm 30/06/14
Loans
Keywords: Monetary policy -- Europe -- Congresses; Monetary policy -- United States -- Congresses; Monetary policy -- Japan -- Congresses; Unemployment -- Europe -- Congresses; Unemployment -- Japan -- Congresses; Unemployment -- United States -- Congresses; Unemployment -- Effect of monetary policy on -- Congresses; Euro-area; Economic policy analysis